2008
DOI: 10.1086/523830
|View full text |Cite
|
Sign up to set email alerts
|

Radial Alignment in Simulated Clusters

Abstract: Observational evidence for the radial alignment of satellites with their dark matter host has been accumulating steadily in the past few years. The effect is seen over a wide range of scales, from massive clusters of galaxies down to galaxy-sized systems, yet the underlying physical mechanism has still not been established. To this end, we have carried out a detailed analysis of the shapes and orientations of dark matter substructures in high-resolution N-body cosmological simulations. We find a strong tendenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(173 citation statements)
references
References 41 publications
(65 reference statements)
12
157
4
Order By: Relevance
“…The tidal torquing mechanism predicts stronger radial alignments at smaller fractions of the virial radius (except at radii where satellite galaxies are at the perihelion of elliptical orbits, Pereira et al 2008). Our uncertainties in Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The tidal torquing mechanism predicts stronger radial alignments at smaller fractions of the virial radius (except at radii where satellite galaxies are at the perihelion of elliptical orbits, Pereira et al 2008). Our uncertainties in Fig.…”
Section: Resultsmentioning
confidence: 71%
“…1 we show some model probability distributions for φ, with periodicity imposed. The short-dashed green line is a fit to the distribution found in the N -body simulations of Pereira et al (2008) while the solid red line is the best fit to our data as described in Section 4 below. The long-dashed blue line shows the uniform distribution.…”
Section: Position Anglementioning
confidence: 97%
See 1 more Smart Citation
“…In both studies, the centroids, axis ratios and position angles of the cluster galaxies have been fixed to the observed light distributions. While studies such as the Sloan Lens ACS Survey indicate that light is generally a good tracer of mass for isolated galaxy lenses in the field (Koopmans et al 2006;Bolton et al 2008a,b), there can be misalignments especially for galaxies in dynamical environments such as in groups and clusters (e.g., Pereira et al 2008). If there are misalignments in the cluster galaxies in Abell 370 and Abell 611, then fixing these lens parameter values to the observed light distribution could lead to a bias in the determination of the halo size.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Ciotti & Dutta (1994) studied the dynamical process of shape changing of an elliptical galaxy under the cluster's tidal field using N-body simulations, and showed an alignment tendency between the galaxies' major axes with the radial direction. Pereira et al (2008) found strong RA of dark matter substructures in a cluster halo in N-body simulations. Usami & Fujimoto (1997) studied a gaseous ellipsoid of uniform density orbiting in the logarithmic potential, and discussed the application of their result to the alignment of galaxies in rich clusters.…”
Section: Introductionmentioning
confidence: 88%